The Impact of a Course in Turkic Cultures on Lithuanian University Students’ Cultural Awareness and Intercultural Skills - Çelik, Servet; Ismailov, Aleksandr; Çaylak, Nuray (Pedagogika, 2016)
With the growing recognition that intercultural skills are a key factor in promoting social justice on a global scale, developing intercultural competence has become an important educational aim. Various approaches to supporting learners in acquiring this skill have been devised; among these are university courses aimed at providing students with information on the history, worldviews and languages of specific cultural groups. In order to ensure that such courses are achieving their aims, it is necessary to understand what motivates students to enroll in them and whether they perceive that their level of intercultural competence has been enhanced by the course content. The researchers designed this study as a means to investigate these issues in the context of an undergraduate course in Turkic cultures offered at a prominent Lithuanian university, using a scalar survey to elicit the views of the participants. The results showed that although the participants felt that the course had increased their awareness of Turkic cultures, as well as increasing their intercultural competence, they expressed only a moderate ability to relate to people of the target culture. This indicates a possible limitation concerning the course content and/or how the material was taught. To address this issue, recommendations for modifying the instructional approach and course materials are provided. These may assist instructors in similar courses in planning content that can effectively enhance students’ intercultural competence.